Chagas disease is related to structural changes of the gut microbiota in adults with chronic infection (TRIPOBIOME Study) - Pérez-Molina, José A.; Crespillo-Andújar, Clara; Trigo, Elena; Chamorro, Sandra; Arsuaga, Marta; Olavarrieta, Leticia; Navia, Beatriz; Martín, Oihane; Monge-Maillo, Begoña; Norman, Francesca F.; Lanza, Val F.; Serrano-Villar, Sergio (PLOS Neglected Tropical Diseases, 2023)
Author summary Chagas disease (CD) affects about 6 million people in endemic areas of the Americas and more than 500,000 people in the rest of the world. This parasitosis is still a neglected disease in which essential knowledge gaps persist regarding its pathogenesis, optimal treatment and prognostic factors. It is well known the relevance of the human microbiome and how significant changes in its composition can affect health. This is the consequence of the importance of microbial communities in immunological and biochemical functions. In this work, we have demonstrated significant changes in the microbiota of subjects with CD who exhibited consistent enrichment of Parabacteroides spp compared to healthy controls while for Enterococcus hirae, Lactobacillus buchneri and Megamonas spp, the effect was less clear once excluded the outliers values. On the other hand, sex, type of visceral involvement and previous treatment with benznidazole did not seem to have a role in gut microbiota structure. Given the current knowledge gaps in our understanding of CD pathogenesis, it will be essential to remain open-minded to other fields in biology.